Expression of the c-myc oncogene under control of an immunoglobulin enhancer in E mu-myc transgenic mice. - Alexander, W S (1987)
Transgenic mice bearing a cellular myc oncogene coupled to the immunoglobulin heavy-chain enhancer (E mu) exhibit perturbed B-lymphocyte development and succumb to B lymphoid tumors. To investigate how the enhancer has affected myc expression, we analyzed the structure and abundance of myc transcripts in tissues of prelymphomatous mice and in the lymphomas. Expression of the E mu-myc transgene appeared to be confined largely to B lymphoid cells, being dominant in bone marrow, spleen, and lymph nodes, with no detectable expression in T cells or other hematopoietic lineages examined. The myc transcripts initiated very predominantly at the normal myc promoters, although use of the more upstream myc promoter was accentuated and an enhancer-associated promoter may be used infrequently. The level of E mu-myc transcripts in the preneoplastic lymphoid tissues and in the E mu-myc tumors was not markedly higher than myc RNA levels in proliferating normal lymphocytes. Thus, enforced expression of structurally normal myc transcripts at only a modestly elevated level has profound biological consequences. The absence of detectable endogenous c-myc RNA in any tumor, or in preneoplastic bone marrow, supports a negative feedback model for normal c-myc regulation.